2016
DOI: 10.3847/0004-637x/819/2/128
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Agn Feedback in Massive Ellipticals With South Pole Telescope Measurements of the Thermal Sunyaev–zel’dovich Effect

Abstract: Energetic feedback due to active galactic nuclei (AGNs) is likely to play an important role in the observed antihierarchical trend in the evolution of galaxies, and yet the energy injected into the circumgalactic medium by this process is largely unknown. One promising approach to constrain this feedback is through measurements of spectral distortions in the cosmic microwave background due to the thermal Sunyaev-Zeldovich (tSZ) effect, whose magnitude is directly proportional to the energy input by AGNs. With … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 135 publications
(202 reference statements)
3
64
2
Order By: Relevance
“…This has been done for massive elliptical systems (with halo mass ∼ 10 14 M ) associated with luminous red galaxies (Hand et al 2011). Others observed systems with halo mass ∼ 10 13 M that have characteristic total energies of 7 × 10 61 ergs in the circumgalactic medium (Planck Collaboration et al 2013;Greco et al 2015;Spacek et al 2016Spacek et al , 2017Spacek et al , 2018Tanimura et al 2019;Pandey et al 2019). These latter studies aim to detect fossil energy from past AGN activity -coincidentally of the same order as the cluster feedback energy scale quoted above.…”
Section: Introductionmentioning
confidence: 99%
“…This has been done for massive elliptical systems (with halo mass ∼ 10 14 M ) associated with luminous red galaxies (Hand et al 2011). Others observed systems with halo mass ∼ 10 13 M that have characteristic total energies of 7 × 10 61 ergs in the circumgalactic medium (Planck Collaboration et al 2013;Greco et al 2015;Spacek et al 2016Spacek et al , 2017Spacek et al , 2018Tanimura et al 2019;Pandey et al 2019). These latter studies aim to detect fossil energy from past AGN activity -coincidentally of the same order as the cluster feedback energy scale quoted above.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of y Θ are direct observables for CMB experiments (e.g., Hand et al 2012;Planck Collaboration et al 2013b;Greco et al 2015;Spacek et al 2016). In fact, trivial modifications to certain kSZ estimators are needed to measure y Θ (e.g., Schaan et al 2016).…”
Section: τ Relationsmentioning
confidence: 99%
“…The signal was detected with a noise level of 0.7µK at 150 GHz. These measurements, along with similar stacked measurements from ACT (Spacek et al 2017), are sensitive enough to place constraints on models of non-gravitational heating (Spacek et al 2018).…”
Section: Large-scale Impact Of Agn Feedback With Stacked Sz Measurementsmentioning
confidence: 89%
“…Similarly, Crichton et al (2016) stacked > 17,000 radio-quiet quasars from the SDSS in ACT data and found 3σ evidence for the presence of associated thermalised gas. The inset panel of Figure 16 illustrates the results of stacking 150 GHz data around 3394 large passive galaxies with an average stellar mass of 1.5 × 10 11 M located outside of large galaxy clusters in the data publicly released by the SPT collaboration (Spacek et al 2016). Note that at 150 GHz the SZ signal appears as a decrement, and this distinguishes it from all emission processes that can contaminate the signal.…”
Section: Large-scale Impact Of Agn Feedback With Stacked Sz Measurementsmentioning
confidence: 98%
See 1 more Smart Citation